Gambaran Kepatuhan Minum Obat Dan Efek Samping Obat Anti Tuberkulosis (Oat) Pada Pasien Tuberkulosis Di Wilayah Kerja Puskesmas Dukuh Dan Kusuma Bangsa Kota Pekalongan - Visabilila, Jihan; Irnawati, Irnawati (PENA NURSING, 2024)
Indonesia holds the second highest ranking globally, after India. The issue of treatment adherence intervention poses a significant difficulty for thosediagnosed with tuberculosis (TB). The occurrence of adverse effects associated with antituberculosis drugsis a contributing factorto thelack ofsuccessin the management of pulmonary tuberculosis. This study aims to determine drug adherence and side effects of anti- tuberculosis drugs in pulmonary TB patients in the area of Kusuma Bangsa Public Health Centers, Pekalongan City. The present study employed a quantitative descriptive methodology with crosssectional approach. The present study involved a sample size of 35 participants who completed the MMAS-8 questionnaire, provided information on pharmacological side effects, and used patient treatment cards. In this study, adherence to medication was observed among 35 respondents. All 35 respondents (100%) demonstrated adherence to the prescribed medication regimen. The reported side effects included a lack of appetite in 6 patients (17.1%), nausea in 16 patients (45.7%), abdominal pain in 4 patients (11.4%), skin redness in 31 patients (88.5%), joint pain in 11 patients (31.4%), fever in 5 patients (14.2%), tingling sensations in 7 patients (20%), skin redness in 6 patients (17.1%), burning sensation in the feet of 3 patients (8.5%), visual disturbances in 6 patients (17.1%), and the ability to differentiate between red and green colors during treatment in 31 patients (88.5%). Although there are many adverse effects from anti-tuberculosis treatments, nurses are expected to always provide health education and motivate patients to stay positive with taking medication.